Large Resistive Switching in Ferroelectric BiFeO3 Nano‐Island Based Switchable Diodes. (28th February 2013) - Hong, Sahwan; Choi, Taekjib; Jeon, Ji Hoon; Kim, Yunseok; Lee, Hosang; Joo, Ho‐Young; Hwang, Inrok; Kim, Jin‐Soo; Kang, Sung‐Oong; Kalinin, Sergei V.; Park, Bae Ho
<x xml:space="preserve">Abstract</x> Comparison between piezoelectric force microscopy images and current‐voltage data consecutively obtained using conductive atomic force microscopy below transition voltages for a highly oriented ferroelectric BiFeO3 nano‐island confirms that ferroelectric polarization reversal induces transitions of forward‐direction, and thus down‐ and up‐polarization is accompanied by positive‐ and negative‐forward diode‐like behavior, respectively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>